Differences in Cognitive Function Between Women and Men With HIV. (1st September 2018) - Maki, Pauline M.; Rubin, Leah H.; Springer, Gayle; Seaberg, Eric C.; Sacktor, Ned; Miller, Eric N.; Valcour, Victor; Young, Mary A.; Becker, James T.; Martin, Eileen M.
Abstract : Background: Women may be more vulnerable to HIV-related cognitive dysfunction compared with men because of sociodemographic, lifestyle, mental health, and biological factors. However, studies to date have yielded inconsistent findings on the existence, magnitude, and pattern of sex differences. We examined these issues using longitudinal data from 2 large, prospective, multisite, observational studies of US women and men with and without HIV. Setting: The Women's Interagency HIV Study (WIHS) and Multicenter AIDS Cohort Study (MACS). Methods: HIV-infected (HIV+) and uninfected (HIV−) participants in the Women's Interagency HIV Study and Multicenter AIDS Cohort Study completed tests of psychomotor speed, executive function, and fine motor skills. Groups were matched on HIV status, sex, age, education, and black race. Generalized linear mixed models were used to examine group differences on continuous and categorical demographically corrected T-scores. Results were adjusted for other confounding factors. Results: The sample (n = 1420) included 710 women (429 HIV+) and 710 men (429 HIV+) (67% non-Hispanic black; 53% high school or less). For continuous T-scores, sex by HIV serostatus interactions were observed on the Trail Making Test parts A & B, Grooved Pegboard, and Symbol Digit Modalities Test. For these tests, HIV+ women scored lower than HIV+ men, with no sex differences in HIV− individuals. In analyses of categorical scores, particularly the Trail Making Test part A and Grooved Pegboard nondominant, HIV+ women also had a higher odds of impairment compared with HIV+ men. Sex differences were constant over time. Conclusions: Although sex differences are generally understudied, HIV+ women vs men show cognitive disadvantages. Elucidating the mechanisms underlying these differences is critical for tailoring cognitive interventions.